Effect of Achillea millefolium on the intensity and duration of menstrual bleeding of women with menorrhagia - Farzaneh Ebrahimi Varzaneh; Fatemeh Nahidi; Faraz Mojab; Mohamad Amin Pourhoseingholi (Mashhad University of Medical Sciences, 2020)
Introduction: Menorrhagia is one of the common gynecological problems and one of the reasons for iron deficiency anemia in women. Regarding to the lack of researches in this field, this study was performed with aim to determine the effect of hydro alcoholic extract of Achillea Milefolium (AM) on Menorrhagia. Methods: This triple-blind randomized controlled clinical trial was performed on 120 women with Menorrhagia referred to Valiasr medical center of Tehran University of Medical Sciences in 2016. Study instruments were demographic form, pictorial blood loss assessment chart (PBAC), weight and meter. After confirming Menorrhagia in basic cycle, the intervention group was treated with 150mg AM capsule and 500mg Mefenamic-acid capsules and the placebo group was treated with AM placebo capsules and Mefenamic-acid capsules every eight hours in seven days of menstruation for two consecutive months. In the next cycle, they were followed-up by the PBAC. Data were analyzed by SPSS software (version 19) and independent t-test, paired t-test, Repeated measurement variance analysis, Friedman, Wilcoxon, Mann-Whitney, Fisher and Chi-square tests (p<0.05). Results: The intensity and duration of menstrual bleeding significantly decreased in both groups (p<0.001). Reduction of intensity and duration of bleeding was significantly higher in the AM group (p<0.001) and duration of bleeding in intervention group was insignificantly higher (p>0.001). Although, intensity and duration of bleeding in both groups increased after the intervention compared with intervention period (p<0.001), but was lower compared with before the intervention (p<0.001). Conclusion: According to the effect of AM on reduction of menstrual bleeding, AM can be used in treatment of Menorrhagia.